The Influence of Serawainese Dialect Context on English Pronunciation (A Descriptive Qualitative Research at The 8th Grade of SMP Negeri 34 Seluma) - Elisa Narvelia; Arif Rahman Hakim; Pebri Prandika Putra (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study examines how eighth-grade students at SMP Negeri 34 Seluma pronounce English in relation to the Serawai dialect. The study was conducted because students with Serawai as their mother tongue often encounter difficulties in pronouncing several English sounds that are absent in their local dialect. The objectives of this research are to identify which aspects of English pronunciation are most affected by the Serawai dialect and to analyze the factors contributing to these difficulties. The study employed a descriptive qualitative method, with data collected through observation, pronunciation tests, and interviews. The findings revealed that the Serawai dialect strongly influences students’ pronunciation, especially in consonant sounds such as /v/, /θ/, /ð/, /ʃ/, and /ʒ/, as well as vowel and diphthong sounds such as /ə/, /ɜː/, /æ/, /əʊ/, /ɪə/, /eə/, and /ʊə/. In addition, the study found four major factors contributing to students’ difficulties: mother tongue interference, lack of pronunciation practice, limited learning methods, and low confidence in speaking English. These findings indicate that pronunciation problems are not caused solely by dialectal influence but also by pedagogical and affective factors. Therefore, teachers are expected to provide more focused pronunciation training, supported by varied methods and consistent practice, to help students overcome these challenges.